Pre- and postoperative evaluation of the effect of reconstructive surgery on patient quality of life and self-esteem: a prospective study of 52 patients - Victor Felipe dos Santos Tejada; Raúl Andrés Mendoza Sassi; Luciano Zogbi Dias; Susi Heliene Lauz Medeiros (Revista Brasileira de Cirurgia Plástica)
Introduction: Benign and malignant skin lesions can affect patients' quality of life and self-esteem; thus, reconstructive plastic surgery is important for these individuals. The objective is to assess the effect of reconstructive plastic surgery on the quality of life (QoL) and self-esteem in patients with benign or malignant skin lesions. Methods: This quasi-experimental "pre-post study" measured QoL using the 36-Item Short Form Health Survey (SF-36) questionnaire. For the measure of self-esteem, the Rosenberg Self-Esteem Scale was used. The changes in scores of both instruments were measured before and after surgery, and the statistical significance of the difference was evaluated using a paired sample t test. The proportion of individuals with an increased QoL score and self-esteem according to sociodemographic variables, lesion or disease characteristics, surgical treatment classification, and stressful events was measured, whereas the statistical significance was assessed using the chi-square test. Results: Fifty-two patients were interviewed. After the surgical intervention, significant improvement in QoL score in most SF-36 domains (emotional, physical, social, pain, general health, and mental health aspects) and improvement in the Rosenberg Self-Esteem Scale score were noted. The factors associated with a higher probability of improvements in QoL and self-esteem after surgery were age =60 years, white skin color, higher education level, occurrence of a stressful event, and malignant neoplasia. Conclusions: Reconstructive surgery positively affected several domains of QoL and self-esteem, showing other improvements in patient health beyond its technical and clinical benefits.